1992
DOI: 10.2307/1940679
|View full text |Cite
|
Sign up to set email alerts
|

Density‐Related Dispersal in Planthoppers: Effects of Interspecific Crowding

Abstract: In dense populations, most planthoppers (Homoptera:Delphacidae) produce fully winged migratory forms that can escape to new habitats. Under less crowded conditions, flightless morphs with reduced wings result. For two sympatric species, Prokelisia marginata and Prokelisia dolus, interspecific crowding was found to be as strong a stimulus for the production of migrants as intraspecific crowding. The effects were reciprocal for both species and were demonstrated both in the laboratory and field. However, because… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
108
2
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(114 citation statements)
references
References 47 publications
2
108
2
2
Order By: Relevance
“…Asymmetric effects of interspecific crowding on wing form have been reported in other studies involving planthoppers (Prokelisia species) in which one species triggered macroptery selectively in the other (Denno & Roderick, 1992). In this study, macropters were produced by the inferior competitor (Prokelisia marginata), which suffered reduced survival and extended development in the presence of the competitive dominant (Prokelisia dolus) (Denno & Roderick, 1992;Denno et al, 2000). Similarly, in the present study, macropters were produced in female N. lugens in the presence of S. furcifera (Fig.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…Asymmetric effects of interspecific crowding on wing form have been reported in other studies involving planthoppers (Prokelisia species) in which one species triggered macroptery selectively in the other (Denno & Roderick, 1992). In this study, macropters were produced by the inferior competitor (Prokelisia marginata), which suffered reduced survival and extended development in the presence of the competitive dominant (Prokelisia dolus) (Denno & Roderick, 1992;Denno et al, 2000). Similarly, in the present study, macropters were produced in female N. lugens in the presence of S. furcifera (Fig.…”
Section: Discussionsupporting
confidence: 67%
“…For example, dispersal capability in flight-dimorphic insects is influenced by various environmental cues such as crowding and host plant condition, temperature, and photoperiod (Harrison, 1980;Roff, 1986;Zera & Denno, 1997). Among these environmental cues, crowding and its interaction with plant quality are thought to be the most influential factors in many insect species, including most delphacid planthoppers (Kisimoto, 1965;Denno et al, 1994;Matsumura, 1996a), however previous studies involving planthoppers and other insects have focused almost entirely on the effects of intraspecific crowding on wing-form determination (Kisimoto, 1965;Morooka et al, 1988;Matsumura, 1996a; but see Denno & Roderick, 1992). This study showed clearly that interspecific crowding also has strong effects on wingform determination and thus dispersal capability in two rice-inhabiting planthopper species, S. furcifera and N. lugens.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Direct interference resulting in mortality for three species of consumers. In the top figure, survivorship of planthoppers decreases with increasing density due to the effects of intraspecific interference mediated indirectly via plant tissue quality [redrawn from Denno and Roderick (1992)]. In the middle figure, the adults of the whitefly parasitioid Encarsia sophia engage in 'host feeding' [redrawn from Jervis and Kidd (1986)], killing conspecific juveniles when they attack previously parasitized whitefly hosts (Collier and Hunter, 2001).…”
Section: Introductionmentioning
confidence: 99%